2008
DOI: 10.1142/s0217732308024468
|View full text |Cite
|
Sign up to set email alerts
|

The Dual Embedding Method in D = 3

Abstract: Improving the beginning steps of a previous work, we settle the dual embedding method (DEM) as an alternative and efficient method for obtaining dual equivalent actions also in D = 3. We show that we can obtain dual equivalent actions which were previously obtained in the literature using the gauging iterative Noether dualization method (NDM). We believe that, with the arbitrariness property of the zero mode, the DEM is more profound since it can reveal a whole family of dual equivalent actions. The result con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…Just few years after its publication, the FJ formalism was modified by Barcelos-Neto and Wotzasek in [38], by Montani and Wotzasek in [39], and through the years it has been used in different systems [40,41].…”
Section: The Faddeev-jackiw Formalismmentioning
confidence: 99%
“…Just few years after its publication, the FJ formalism was modified by Barcelos-Neto and Wotzasek in [38], by Montani and Wotzasek in [39], and through the years it has been used in different systems [40,41].…”
Section: The Faddeev-jackiw Formalismmentioning
confidence: 99%
“…Furthermore, the matrix (22) is still singular; however, we have shown that there are no more constraints and that the theory has a gauge symmetry. In order to construct a symplectic tensor, we need to fix the gauge [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25], and thus we will fix the temporal gauge, say, 0 = 0 = 0, which means thaṫ= 0 anḋ= 0. In this manner, the fixing gauge will be added to the symplectic Lagrangian via Lagrange multipliers, Θ and Ξ .…”
Section: (22)mentioning
confidence: 99%
“…In this manner, with the antecedents mentioned above, in this paper, we will study the P-CS theory from a symplectic point of view. For this aim, we will use the symplectic formalism of Faddeev-Jackiw [FJ] [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25], due basically to the fact that the FJ approach is more economical than Dirac's method. In fact, the FJ is a symplectic description where all relevant information of the theory can be obtained through a symplectic tensor, which is constructed from the symplectic variables that are identified from the Lagrangian.…”
Section: Introductionmentioning
confidence: 99%
“…In recent works [6], the FJ symplectic formalism has been used in a systematic way for different purposes: the study of hidden symmetries, the construction of equivalent gauge theories (duality), noncommutative field theory, to solve the obstruction problem to the construction of the canonical Lagrangian formulation for rotational systems and other.…”
Section: Introductionmentioning
confidence: 99%